2020
DOI: 10.21608/pssjn.2021.50276.1065
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Nursing Work Environment, Patient Safety Culture, and Missed Nursing Care Among Staff nurses

Abstract: Background: The environment of work and culture of patient safety are crucial factors that had a major effect on missing nursing care. Aim: To explore the relationships between the work environment, patient safety culture, and missed nursing care among staff nurses. Method: Descriptive correlational design was used. The study included a convenience sample of 136 staff nurses who were working at all inpatient units of main Mansoura university hospital. Work environment scale, patient safety culture scale, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Nursing managers also share their views on the importance of safety, fidelity and accountability, and agreed trust in the effectiveness of preventive measures. This result was consistent with Ibrahim and Abo Habieb (2020) who found that a majority of the nurses who were studied had good or moderate perception (66%) toward patient safety culture. In the same line El-Sherbiny et al, (2020) reported that the lowest score was for communication openness.…”
Section: Table (8)supporting
confidence: 90%
“…Nursing managers also share their views on the importance of safety, fidelity and accountability, and agreed trust in the effectiveness of preventive measures. This result was consistent with Ibrahim and Abo Habieb (2020) who found that a majority of the nurses who were studied had good or moderate perception (66%) toward patient safety culture. In the same line El-Sherbiny et al, (2020) reported that the lowest score was for communication openness.…”
Section: Table (8)supporting
confidence: 90%
“…A comprehensive multifaceted approach from all healthcare disciplines and actors considered to be a key for identifying and managing potential risks to patient safety (Muftawu& Aldogan, 2020).Also, patient safety is a field in the health profession in which one goal is to achieve a trustworthy healthcare delivery through the application of safety science methods. It is an attribute of healthcare system aim at alleviating the incidence and effect of adverse events (Alotaibi& Federico, 2017).To improve healthcare quality, there is the need to establish a culture of safety which requires an understanding of the values, beliefs, and norms about what is important in an organization, and what attitudes and behaviors related to patient safety are expected and appropriate (AlDoweri, et al, 2015).The current study showed about personal data of staff nurses; in relation to age there were more than two thirds had(22)(23) years old with mean age score (31.77+87.25). Regarding marital status, there were more than two third of staff nurses married, and highest percentage of staff nurses had diploma degree.…”
mentioning
confidence: 68%
“…Table(1) shows the personal data of the staff nurses, in relation to age there are (68.2%) have(22)(23) years old with mean age score…”
mentioning
confidence: 99%
“…this perception may because each nursing unit is distinct and because each unit manages its own safety culture, this has a bigger influence on staff members' behavior. It is crucial for bedside nurses to discuss safety concerns they come across in the course of their job and offer solutions for enhancing the patient safety culture.Similarly,Ibrahim and Habieb, (2020) who reported that the most nurses had good perception toward patient culture. In the same line the study ofRicklin, Hess, and Hautz (2019), and Ali et al(2018) supported these findings.…”
mentioning
confidence: 96%